EVALUATION OF THE FEASIBILITY OF PUBLIC TRANSPORT VEHICLES FUEL CONVERSION IN JABOTABEK AREA - Yusep K Caryana (Scientific Contributions Oil and Gas, 2001)
NGV has been used as a vehicular fuel in Indonesia, particularly in Jakarta. However, the success of this NGV utilization is still in question. Currently, only taxicabs and a view dedicated buses have successfully utilized NGV for us fuel.